A New End Group on Nonfullerene Acceptors Endows Efficient Organic Solar Cells with Low Energy Losses. (21st November 2021) - Pan, Youwen; Zheng, Xiangjun; Guo, Jing; Chen, Zeng; Li, Shuixing; He, Chengliang; Ye, Shounuan; Xia, Xinxin; Wang, Shanlu; Lu, Xinhui; Zhu, Haiming; Min, Jie; et al.
Abstract: Large energy loss is one of the main limiting factors for power conversion efficiencies (PCEs) of organic solar cells (OSCs). To this effect, the chemical modifications of the famous Y‐series nonfullerene acceptor (NFA) BTP‐4Cl‐BO with a new end group, TPC‐Cl, whose π‐conjugation is extended through the fusing of 3‐(dicyanomethylene)indanone (IC) group with a chlorinated thiophene ring, to synthesize two novel NFAs, BTP‐T‐2Cl and BTP‐T‐3Cl are performed. For BTP‐T‐2Cl with two TPC‐Cl groups, the resulting OSC exhibits a modest PCE of 14.89% but an extraordinary low energy loss of 0.49 eV, because its superior electroluminescence quantum efficiency of 0.0606% mitigates significantly the nonradiative loss (0.191 eV). For BTP‐T‐3Cl with one TPC‐Cl group, the corresponding device shows a higher PCE of 17.61% accompanied by a slightly bigger energy loss of 0.51 eV, which can be ascribed to the optimized morphology and/or efficient charge generation. Furthermore, the ternary OSC adopting two NFAs of BTP‐T‐3Cl and BTP‐4Cl‐BO achieves an impressive PCE of 18.21% (certified value of 17.9%), which is among the highest values for OSCs to date. The above results demonstrate that expanding end groups of NFAs with electron‐donating rings is an effective strategy to realize lower energy losses for OSCs. Abstract : A new end group by extending π‐conjugation with a chlorinated thiophene ring is reported. Acceptors with strong luminescence brought about by the end group realizes energy loss mitigation of organic solar cells. Thus, the efficiencies of 17.61% and 18.21% for the binary and ternary devices are exhibited by the chemical modification of the end group.